Risky mindset: prior exposure to risk increases utilitarian choices in sacrificial moral scenarios - Sahai, Abhishek; Manjaly, Jaison A. (Frontiers in Behavioral Economics, 2024)
Evidence of cross-domain spillover into the moral domain has been limited to altruistic and consumption behavior. Building upon the literature of spillover effects and domain-general decision processes, we predicted that choice behavior in the economic domain would affect subsequent choices in sacrificial moral dilemmas. We tested this prediction using hypothetical risky gambles and vignettes for moral dilemmas. We found that prior exposure to risky gambles increased utilitarian responses towards sacrificial moral dilemmas. Mediation analysis suggests that this is due to spillover of cost-benefit mindset. This mindset increases the probability of making utilitarian-type choices when faced with moral dilemmas but does not affect moral judgment. These results suggest that moral decisions are susceptible to cross-domain spillover effects. Moral values might get easily traded-off in transactional scenarios where cost-benefit analysis is a dominant decision strategy.